Chaotic Multiple Access System Based on Orthogonal Chaotic Vector of Lorenz System - Abdullah, Hikmat N. (Nahrain University College of Engineering Journal, 2017)
Chaos phenomenon is capable of generating chaotic sequences with low cross-correlation, which can be useful for spreading the direct sequence code division multiple access (DS-CDMA) system. In this paper, a chaotic multiple access communication system based on Orthogonal Chaotic Vector (OCV) generated from Lorenz system has been proposed. The simulation results show that the performance of the proposed system is almost the same regardless of the number of users in Additive White Gaussian noise AWGN channel. The results also show that at bit-error-rate of 10-3, the proposed system has achieved gains of 6 dB and 11 dB in signal-to-noise ratio over traditional DS-CDMA based on Walsh-Hadamard sequence in AWGN and Rayleigh fading channels, respectively.